Integrating Indonesian Cultural Aspects in Bahasa Indonesia bagi Penutur Asing (BIPA) Textbooks “Sahabatku Indonesia” - Fitria, Tira Nur (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
This research describes the cultural aspects of the BIPA textbook “Sahabatku Indonesia”. This research applies a qualitative content analysis. Several cultural aspects are found in the BIPA book levels B1, B2, C1, and C2. BIPA Book level B1 shows the traditional transportation of Becak, the traditional medicine Kerokan, a side dish Tempe, the cultural heritage of Tenun, a traditional dance Tari Sama, a traditional ceremony of the coast Melasti in Bali, the traditional dance Tari Jaipong dan Tari Lilin, folklore Sangkuriang, Bawang Merah dan si Bawang putih, and Timun Mas, traditional martial art Pencak Silat. BIPA Book level B2 shows, Batik Craftsmen. herbal medicine or Jamu, Dalang (player Wayang puppet), tourism place Curug Malela and Mount Bromo, culture a sacred offering Sesajen Bali, historical place Gedung Merdeka, belief toward prohibition/taboo, cultural art Reog Ponorogo, folklore Malin Kundang and Riwayat Si Batu, tradition Merantau, game Panjat Pinang and Balap Karung on Celebrating Independence Day, a celebration of Hari Kartini and Hari Guru, national heroes of Mohammad Hatta and Dewi Sartika, and social class in Javanese culture Priyayi. In BIPA Book level C1 shows the tourist place Borobudur Temple, traditional cloth Batik, tradition of Mudik during Eid al-Fitr, traditional musical instrument Angklung, fable story of Gajah dan Semut, Javanese traditional wedding ceremony, traditional funeral ceremony in Toraja. Indonesian food Opor Ayam and Nasi Goreng, regional specialty coffee, a national hero of RA Kartini, and traditional dance Tari Piring. BIPA Book level C2 shows only shows Indonesian snacks and food Serabi/Surabi.